Efficacy and safety of endoscopic fenestration for treating giant middle cranial fossa arachnoid cysts in pediatrics - Guo, Huachao; Ma, Zhen; Lv, Qiang; Li, Tao; Dong, Liujian; Yu, Jinliang; Feng, Shubin; Wang, Yushe (Frontiers in Pediatrics, 2025)
ObjectiveA middle cranial fossa is a well-recognized location for an intracranial arachnoid cyst in children. Giant middle fossa arachnoid cysts (GMFACs) can compress brain tissue, leading to rupture and potentially developing a subdural hygroma or hematoma. With recent advancements in neuroendoscopic technology, neuroendoscopic treatments have increasingly been used for middle fossa cysts. However, the risk of subdural effusion or hematoma is higher postoperatively, and the treatment for subdural effusion remains inconclusive. This study aimed to explore the safety and efficacy of this technology by evaluating the clinical and radiological outcomes of endoscopic fenestration for these cysts.MethodsA retrospective review of the operative procedures database identified 26 procedures performed to fenestrate GMFACs at the Neurosurgery Department of Henan Provincial Children's Hospital. The minimum follow-up period exceeded 6 months.ResultsA total of 26 patients were included between 2016 and 2021. Among the 26 patients, 19 were male, with a mean age of 3.56 ± 2.98 years; 13 were under 2 years. With the applied technique, the cyst volume reduction rate was 76.9% (n = 20). A reduction of more than 50% in middle fossa arachnoid cyst volume was achieved in 57.7% of all patients (n = 15). In five cases (19.2%), the cyst had disappeared by the follow-up date, or its volume reduction exceeded 90%. Symptom improvement or resolution was observed in 13 of the 15 patients (86.7%). The postoperative subdural effusion rate was 53.8% (n = 14). Among these, 64.2% (9/14) of the children experienced complete absorption of subdural effusion, with a mean duration of 5.38 ± 5.37 months. Only 21.4% (3/14) of the children had subdural effusion requiring further surgery. The overall patient reoperation rate was 11.5% (3/26). The multivariate logistic regression analysis results showed that age under 2 years was not associated with postoperative subdural effusion (p = 0.119) or the need for reoperation (p = 0.786).ConclusionsThis study analyzed the efficacy of endoscopic treatment in a predominantly treated patient cohort with GMFACs, as indicated by improved clinical symptoms and reduced radiological volume after treatment. Furthermore, This study has shown that age is neither the cause of subdural effusion nor the leading cause of secondary surgery. Most subdural effusions in children can be absorbed within a few months after surgery, and only a few children need subsequent surgical treatment. Endoscopy is a safe technique for managing giant middle fossa cysts, including younger children.